(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يهدف البحث إلى تعرف فاعلية الألعاب التعليمية في تحصيل تلامذة الصف الأول الأساسي، واعتمد البحث على المنهج التجريبي. تكونت العينة من (68) تلميذاً وتلميذةً من الصف الأول من مدارس التعليم الأساسي في مدينة جبلة، اختيروا بطريقة عشوائية، في الفصل الأول من العام الدراسي /2012/2013/، ولجمع البيانات استخدم: الاختبار التحصيلي لقياس فاعلية الألعاب التعليمية على تلامذة المجموعة التجريبية. وأظهرت النتائج وجود فروق دالة إحصائياً بين متوسطات المجموعة التجريبية ومتوسطات المجموعة الضابطة لصالح تلامذة المجموعة التجريبية, وتفوق تلامذة المجموعة التجريبية على تلامذة المجموعة الضابطة, كما بيَّنت عدم وجود فروق بين ذكور وإناث المجموعة التجريبية، وتفوق كل منهما على ذكور وإناث المجموعة الضابطة, وأثبتت ارتفاع متوسط درجات تلامذة المجموعة التجريبية في القياس البعدي مقارنة بمتوسطاتهم في القياس القبلي, وخلص البحث إلى مقترحات منها: استخدام الألعاب التعليمية في مختلف المواد التعليمية ولمختلف الصفوف الدراسية, وتوجيه القائمين على إعداد الكتب المدرسية إلى ضرورة تزويدها بألعاب تعليمية في الموضوعات المختلفة. This study seeks to identify the effectiveness of educational games in the achievement of students in the first grade. It adopts an experimental method. The sample consisted of (68) pupils from the first grade of basic schools in Jableh City, randomly selected during the first semester (2012/2013). To collect the data we used achievement test to measure the effectiveness of educational games in the development of some scientific concepts by students of the experimental group. Results revealed that there were differences between the averages of the experimental group and the control group averages. Students of the experimental group were more successful than control group. There were no differences between male and female experimental group. Results also demonstrated higher average grades by students in the experimental group in the past-test compared to their averages in pre-test. The research recommends use of educational games on different materials and for different grades. Textbooks should also be provided with educational toys in different subjects.